Application of the Stampacchia lemma to anisotropic degenerate elliptic equations - Hichem (Journal of Innovative Applied Mathematics and Computational Sciences, 2023)
In this paper, we prove the existence and regularity of solutions for a class of nonlinear anisotropic degenerate elliptic equations with the data f belonging to certain Marcinkiewicz spaces Mm(Ω) with m > 1. We use a generalized Stampacchia Lemma version to establish the main results.